Answer:
A y = -4x + 2
Step-by-step explanation:
<em>1</em><em>)</em><em> </em><em>x, <u>y</u></em><em> </em><em>= -2, <u>10</u></em>
y = -4x + 2
y = -4 . -2 + 2
y = 8 + 2
<u>y</u> = <u>10</u>
<em>2</em><em>)</em><em> </em><em>x</em><em>,</em><em> </em><em><u>y</u></em><em> </em><em>=</em><em> </em><em>0</em><em>,</em><em> </em><em><u>2</u></em>
y = -4x + 2
y = -4 . 0 + 2
<u>y</u> = <u>2</u>
<em>3</em><em>)</em><em> </em><em>x</em><em>,</em><em> </em><em><u>y</u></em><em> </em><em>=</em><em> </em><em>1</em><em>,</em><em> </em><em>-</em><em><u>2</u></em>
y = -4x + 2
y = -4 . 1 + 2
y = -4 + 2
<u>y</u> = <u>-2</u>
<em>4</em><em>)</em><em> </em><em>x</em><em>,</em><em> </em><em><u>y</u></em><em> </em><em>=</em><em> </em><em>3</em><em>,</em><em> </em><em>-</em><u><em>1</em><em>0</em></u>
y = -4x + 2
y = -4 . 3 + 2
y = -12 + 2
<u>y</u> = <u>1</u><u>0</u>
<h3>#CMIIW</h3>